Long-term ambient air pollution exposure and renal function and biomarkers of renal disease - Karl Kilbo Edlund; Yiyi Xu; Eva M. Andersson; Anders Christensson; Mats Dehlin; Helena Forsblad-d'Elia; Florencia Harari; Stefan Ljunggren; Peter Molnár; Anna Oudin; Magnus Svartengren; Petter Ljungman; et al. (BMC, 2024)
Abstract Background Despite accumulating evidence of an association between air pollution and renal disease, studies on the association between long-term exposure to air pollution and renal function are still contradictory. This study aimed to investigate this association in a large population with relatively low exposure and with improved estimation of renal function as well as renal injury biomarkers. Methods We performed a cross-sectional analysis in the middle-aged general population participating in the Swedish CardioPulmonary bioImaging Study (SCAPIS; n = 30 154). Individual 10-year exposure to total and locally emitted fine particulate matter (PM2.5), inhalable particulate matter (PM10), and nitrogen oxides (NOx) were modelled using high-resolution dispersion models. Linear regression models were used to estimate associations between exposures and estimated glomerular filtration rate (eGFR, combined creatinine and cystatin C) and serum levels of renal injury biomarkers (KIM-1, MCP-1, IL-6, IL-18, MMP-2, MMP-7, MMP-9, FGF-23, and uric acid), with consideration of potential confounders. Results Median long-term PM2.5 exposure was 6.2 µg/m3. Almost all participants had a normal renal function and median eGFR was 99.2 mL/min/1.73 m2. PM2.5 exposure was associated with 1.3% (95% CI 0.6, 2.0) higher eGFR per 2.03 µg/m3 (interquartile range, IQR). PM2.5 exposure was also associated with elevated serum matrix metalloproteinase 2 (MMP-2) concentration, with 7.2% (95% CI 1.9, 12.8) higher MMP-2 per 2.03 µg/m3. There was a tendency towards an association between PM10 and higher levels of uric acid, but no associations were found with the other biomarkers. Associations with other air pollutants were null or inconsistent. Conclusion In this large general population sample at low exposure levels, we found a surprising association between PM2.5 exposure and a higher renal filtration. It seems unlikely that particle function would improve renal function. However, increased filtration is an early sign of renal injury and may be related to the relatively healthy population at comparatively low exposure levels. Furthermore, PM2.5 exposure was associated with higher serum concentrations of MMP-2, an early indicator of renal and cardiovascular pathology.